Reduced wrist flexor H-reflex excitability is linked with increased wrist proprioceptive error in adults with cerebral palsy - Dukkipati, S. Shekar; Walker, Sarah J.; Trevarrow, Michael P.; Busboom, Morgan; Baker, Sarah E.; Kurz, Max J. (Frontiers in Neurology, 2022)
Although most neurophysiological studies of persons with cerebral palsy (CP) have been focused on supraspinal networks, recent evidence points towards the spinal cord as a central contributor to their motor impairments. However, it is unclear if alterations in the spinal pathways are also linked to deficits in the sensory processing observed clinically. This investigation aimed to begin to address this knowledge gap by evaluating the flexor carpi radialis (FCR) H-reflex in adults with CP and neurotypical (NT) controls while at rest and during an isometric wrist flexion task. The maximal H-wave (Hmax) and M-wave (Mmax) at rest were calculated and utilized to compute Hmax/Mmax ratios (H:M ratios). Secondarily, the facilitation of the H-wave was measured while producing an isometric, voluntary wrist flexion contraction (i.e., active condition). Lastly, a wrist position sense test was used to quantify the level of joint position sense. These results revealed that the adults with CP had a lower H:M ratio compared with the NT controls while at rest. The adults with CP were also unable to facilitate their H-reflexes with voluntary contraction and had greater position sense errors compared with the controls. Further, these results showed that the adults with CP that had greater wrist position sense errors tended to have a lower H:M ratio at rest. Overall, these findings highlight that aberration in the spinal cord pathways of adults with CP might play a role in the sensory processing deficiencies observed in adults with CP.